Boko Haram’s Terrorism and the Nigerian State: Federalism, Politics and Policies - Faluyi, Olumuyiwa Temitope (Advances in African Economic, Social and Political Development, 2019)
Chapter 1: Nigerian State in Arms: It Begins -- Chapter 2:Terrorism: An Overview -- Chapter 3: Character of the Nigerian State -- Chapter 4: The Resource-State: A Theoretical Reality -- Chapter 5: Boko Haram: A Reign of Terror -- Chapter 6: Nigeria's Counter-Terrorism Strategies -- Chapter 7: Nigeria's Counter-Terrorism Strategies: Implications for Nigerian Federalism -- Chapter 8: Towards the Sustainable De-Securitization of Terrorism